Delivering effective speeches workshop: workshop series 3 / Nazima Versay Kudus - Versay Kudus, Nazima (e-Lingua, Academy of Language Studies, UiTM, 2022)
Alas, the third workshop series of English for University Professionals was successfully conducted among lecturers from various faculties at Universiti Teknologi MARA, Cawangan Pulau Pinang on January 14, 2022 from 3.00 p.m to 5.00 p.m. The session was conducted online on Google Meet platform. The 30 participants were divided into six small groups which ran concurrently. The facilitators were Assoc. Prof. Dr. Mah Boon Yih, Nazima Versay Kudus, Wan Noorli Razali, Marni Jamil, Nur Afiqah Ab. Latif and Noraziah Mohd Amin.